2016
DOI: 10.1080/2162402x.2016.1196299
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages promote matrix protrusive and invasive function of breast cancer cells via MIP-1β dependent upregulation ofMYO3Agene in breast cancer cells

Abstract: The potential of a tumor cell to metastasize profoundly depends on its microenvironment, or "niche" interactions with local components. Tumor-associated-macrophages (TAMs) are the most abundant subpopulation of tumor stroma and represent a key component of tumor microenvironment. The dynamic interaction of cancer cells with neighboring TAMs actively drive cancer progression and metastatic transformation through intercellular signaling networks that need better elucidation. Thus, current study was planned for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Their expression has been found in tumor-associated and cancer cells. In a tumor, they are produced by TAM [ 69 , 124 , 125 , 126 , 127 ], MDSC [ 68 ], and MSC [ 66 ], which promotes tumor growth. The expression of CCL4 may also occur in tumor-associated neutrophils (TAN) [ 128 ].…”
Section: Ccr5 Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their expression has been found in tumor-associated and cancer cells. In a tumor, they are produced by TAM [ 69 , 124 , 125 , 126 , 127 ], MDSC [ 68 ], and MSC [ 66 ], which promotes tumor growth. The expression of CCL4 may also occur in tumor-associated neutrophils (TAN) [ 128 ].…”
Section: Ccr5 Ligandsmentioning
confidence: 99%
“…CCL3 causes migration and invasion of cancer cells via CCR5 [ 124 , 127 , 144 ]. This is related, among other things, to the activation of PI3K→Akt/PKB and ERK MAPK pathways [ 127 ].…”
Section: Ccr5 Ligandsmentioning
confidence: 99%
“…It was found that human breast cancer specimens exhibited significant association between mRNA expression levels of MIP-1β and MYO3A and both, whether MIP-1β and MYO3A showed positive correlation with an established molecular determinant of cancer cell invasion, MMP9. Higher expression of these genes correlated with poor survival of breast cancer patients (Baghel et al, 2016). …”
Section: Metastatic Nichesmentioning
confidence: 99%
“…Besides, MIP‐1β critically involved in peripheral monocyte activation and adipose tissue infiltration resulting in an overweight or obese status, which has a higher risk for EC . In addition, Baghel et al . reported that MIP‐1β could enhance the invasive potential of metastatic breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%